Hemodynamic responses to handgrip and metaboreflex activation are exaggerated in individuals with metabolic syndrome independent of resting blood pressure, waist circumference, and fasting blood glucose - Stavres, Jon; Aultman, Ryan A.; Brandner, Caleb F.; Newsome, Ta’Quoris A.; Vallecillo-Bustos, Anabelle; Wise, Havens L.; Henderson, Alex; Stanfield, Diavion; Mannozzi, Joseph; Graybeal, Austin J. (Frontiers in Physiology, 2023)
Prior studies report conflicting evidence regarding exercise pressor and metaboreflex responses in individuals with metabolic syndrome (MetS). Purpose. To test the hypotheses that 1) exercise pressor and metaboreflex responses are exaggerated in MetS and 2) these differences may be explained by elevated resting blood pressure. Methods. Blood pressure and heart rate (HR) were evaluated in 26 participants (13 MetS) during 2 minutes of handgrip exercise followed by 3 minutes of post-exercise circulatory occlusion (PECO). Systolic (SBP), diastolic (DBP), and mean arterial pressure (MAP), along with HR and a cumulative blood pressure index (BPI), were compared between groups using independent samples t-tests, and analyses of covariance were used to adjust for differences in resting blood pressure, fasting blood glucose (FBG), and waist circumference (WC). Results. ΔSBP (~78% and ~54%), ΔMAP (~67% and ~55%), and BPI (~16% and ~20%) responses were significantly exaggerated in individuals with MetS during handgrip and PECO, respectively (all p<0.04). ΔDBP, ΔMAP, and BPI responses during handgrip remained significantly different between groups after independently covarying for resting blood pressure (p<0.01), and after simultaneously covarying for resting blood pressure, FBG, and WC (p<0.03). Likewise, peak SBP, DBP, MAP, and BPI responses during PECO remained significantly different between groups after adjusting for resting blood pressure (p<0.02), with peak SBP, MAP, and BPI response remaining different between groups after adjusting for all three covariates simultaneously (p<0.04). Conclusions. These data suggest that exercise pressor and metaboreflex responses are significantly exaggerated in MetS independent of differences in resting blood pressure, FBG, or WC.